Brand Endorsers with Role Model Function: Social Media Influencers’ Self-Perception and Advertising Literacy - Kühn, Jessica; Riesmeyer, Claudia (MedienPädagogik, 2021)
Social media influencers (SMIs) are taking on new roles in the communication environment of their followers as persuasive agents, opinion leaders, brand endorsers, and role models. Taking a look from the perspective of SMIs as agents in the persuasion attempt and their advertising literacy, our study has three aims. First, we provide insight into SMIs‘ self-perception as opinion-leading brand endorsers. Second, we discuss the extent to which SMIs use this awareness of and knowledge about their role model function for their particular young followers. Finally, we show how SMIs actively construct their media persona and how their relationship with their followers is based around this identity. The results from 15 semi-structured, guideline-based interviews conducted in 2019 with German SMIs working in different subject areas (e.g., fitness, fashion, travel, and family) show that SMIs are advertising literate. SMIs are aware of their multiple roles (understanding of one‘s roles: conceptional dimension), and reflect about their media persona‘s role model function (role interpretation: attitudinal dimension). Therefore, the majority of SMIs create their content and their media persona, as well as actively construct their relationship to their followers, based on their knowledge and awareness (role construction: performance dimension). Sogenannte Social Media Influencer*innen (SMI) übernehmen als Werbebotschafter, mediale Entscheidungsträger, Online-Meinungsführer und Kommunikationspartner eine neue Rolle in der Kommunikationsumgebung ihrer Follower*innen. Basierend auf dem Persuasion Knowledge Model und der Konzeption von Werbekompetenz bestehend aus den Dimensionen Wissen, Einstellung und Handeln untersucht die Studie, wie SMI ihre mediale Rolle konstruieren, inwiefern sie sich ihrer Vorbildrolle für die insbesondere jungen Follower*innen bewusst sind und wie sie mit ihren Followern*innen interagieren. Im Jahr 2019 wurden fünfzehn halbstrukturierte leitfadengestützte Interviews mit SMI in Deutschland geführt, die in verschiedenen Themenbereichen tätig sind (z.B. Fitness, Mode, Reisen, Familie). Die Ergebnisse zeigen, dass SMI als werbekompetent gekennzeichnet werden können: Sie kennen ihre Funktionen (Rollenverständnis: Wissensdimension) und sind sich der damit verbundenen Wirkung ihres medialen Auftritts auf ihre Follower*innen bewusst (Rolleninterpretation: Einstellungsdimension). Auf Basis dieses Wissens und des Bewusstseins wählen sie konkret Inhalte für die Selbstdarstellung aus, konstruieren ihr mediales Erscheinungsbild bewusst und entscheiden sich proaktiv, inwieweit sie mit ihren Follower*innen interagieren (Rollenkonstruktion: Handlungsdimension).